ANALISIS KEBERLANJUTAN USAHATANI PADI SAWAH DI KELURAHAN BARUGA KECAMATAN BARUGA KOTA KENDARI - Riska, Riska; Salahuddin, Salahuddin; Lasinta, Megafirmawanti; Mihrad, Edy Syah (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2025)
This study aimed to analyze the sustainability of paddy farming in Baruga Village, Baruga District, Kendari City. The population of this study was 280 paddy farmers. The sample of this study was 28 paddy farmers (10% of the population) taken by simple random sampling. The data analysis of this study used descriptive statistics. Descriptive statistics to describe or describe the state of the research variables. The results of the study indicate that the sustainability of paddy farming in Baruga Village, Baruga District, Kendari City is in the medium category. Paddy farming in Baruga Village, Baruga District, Kendari City has fulfilled the sustainability of economic, social and environmental aspects but the sustainability of economic aspects and sustainability of environmental aspects needs to be improved. Sustainability from the economic aspect and sustainability from the ecological aspect is in the medium category. As for the sustainability of the social aspect has been in the high category.